Trophic studies on the Okhotsk Sea herring in the 2000s (food composition, daily rations, assessment of consumption in the annual cycle) - Konstantin M. Gorbatenko; Igor V. Melnikov (Известия ТИНРО, 2016)
Daily ration of the Okhotsk Sea herring is estimated as 3.9 % of the body weight in spring, 7.7 % in summer, 4.9 % in autumn, and 1.2 % in winter. Its mean annual consumption is assessed as 35.9 million t of prey, mainly zooplankton (97.3 % of the ration) including 15.86 · 106 t of euphausiids (43.0 %), 15.16 · 106 t of copepods (41.1 %), and 2.7 · 106 t of amphipods (6.2 %). In total, 6.9 % of the Euphausia stock, 3.7 % of the Copepoda stock, 9.7 % of the Amphipoda stock, and 0.1 % of the Chaetognatha stock are grazed by herring annually. The herring consumption is on average 18.9 % of the total volume of food consumed by nekton in the epipelagic layer of the Okhotsk Sea.